Predicting Clothing Behaviour of Generation Z Men and Women through Self Esteem and Body Appreciation - Baijal, Devyani (My University, 2024)
The purpose of this study is to look into how Generation Z individuals' dress choices, body image, and self-esteem relate to one another. Studying how young men and women in this age range perceive themselves and their bodies shapes the clothes they wear is the main goal of the research. The variables of self-esteem, body appreciation, and wardrobe choices will be investigated using a quantitative research approach that makes use of surveys and statistical analysis. It is anticipated that the study's findings will offer important new perspectives on the elements influencing Generation Z's clothing choices, including how body image and self-perception influence looks. There were 162 participants in the study (N=162), 81 of whom were male and 81 of whom were female, with ages ranging from 12 to 27. This study is a modest attempt to use regression analysis, correlation analysis and T- Test to examine the relationship between the variables listed above.
Keywords: Generation Z; Clothing behavior; Self-esteem; Body Appreciation, Men, Women.